Barriers and facilitators to prostate cancer screening, early presentation and diagnosis-experiences of men diagnosed with prostate cancer in Kenya - Waihenya, Charles; Thumbi, S. M.; Ojuka, Daniel Kinyuru; Ragin, Camille; Zeigler-Johnson, Charnita (Frontiers in Cancer Control and Society, 2025)
PurposeTo identify the barriers and facilitators to help seeking, and screening for early presentation and diagnosis of prostate cancer in Kenya.MethodsSeven focus group discussions (FGDs) were held with a total of 46 patients diagnosed and living with prostate cancer, 65% (n = 30) from a public Hospital and 35% (n = 16) from a private hospital. An FGD guide was used to collect data on patients' barriers and facilitators of prostate cancer screening, help seeking, and diagnosis.ResultsThe patients were distributed across different age groups: 4.3 % (n = 2) were aged 50–59, 41% (n = 19) were aged 60–69, and 54% (n = 25) were aged 70 and above. The majority of the patients were in the 7th and the 8th decade 41% (n = 19) and 54% (n = 25), respectively. A larger population had at least secondary and tertiary education 39% (n = 18) and 35% (n = 16) respectively. Retired patients constituted 33% (n = 15), employed at 28% (n = 13), and 28% (n = 13) were unable to work. The main themes emerging from this study were barriers to help seeking: Lack of awareness of symptoms, symptoms misattribution and management associated stigma, impact on libido and perceptions, beliefs about prostate cancer and economic factors and financial constraints. Others were misdiagnosis, inadequate health infrastructure and failure to disclose diagnosis. Interventions emerging from the interviews were cultural sensitization and education programs, public education and awareness campaigns, positive masculinity messages and an option for gender-matched health providers.ConclusionThe delay in early presentation and diagnosis of prostate cancer is a result of the complex interplay of multiple factors. This underscores the need for a multifaceted approach to improving early presentation and diagnosis of prostate cancer. Recognizing this complexity is crucial for the development of effective holistic strategies to improve timely presentation and diagnosis and ultimately health outcomes for men at risk of prostate cancer.